Xerostomia And Its Effect On Oral Microbial Growth: An Overview (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Dry mouth caused by decreased or absent salivary flow is known as xerostomia. Although xerostomia is not a disease, it can be a sign of several illnesses, a side effect of drugs, or a result of radiation exposure. When xerostomia is untreated, it can lower the pH levels of the mouth and create a favorable environment for the growth of certain microflora, such as Streptococci, Actinomycetes, and Lactobacilli, that can lead to dental cavities, fungal infections, and other problems.       Numerous causes, problems, preventative strategies, and treatment modalities are covered in detail in this analysis. Dehydration, damage to the salivary glands, and disruption of neuronal transmission are the main causes of xerostomia. Acting on the cause, preserving salivary function, and avoiding complications are all examples of preventive approaches. There are four primary approaches to treating xerostomia: symptomatic or palliative, systemic and local stimulation, and preventing complications.The aim of this investigation is to clarify xerostomia, its causes, its complications, its prevention, treatment, and its effect on oral microbial growth. From this review we conclude that the patient's oral and overall health are impacted by xerostomia, or dry mouth, which lowers their quality of life.